2012
DOI: 10.1080/17450128.2011.635723
|View full text |Cite
|
Sign up to set email alerts
|

Access to conception planning information and services for people living with HIV in Ontario, Canada: A community-based research study

Abstract: Decreased mortality, decreased risk of vertical HIV transmission, and many people living with HIV (PLWHIV) being of reproductive age have led many PLWHIV to consider pregnancy. However, scarce data exist regarding the conception planning resources required and available for PLWHIV to have safe and healthy pregnancies. This study aimed to identify gaps between the need for, knowledge of, and access to conception planning information and services among PLWHIV in Ontario, Canada. PLWHIV from three large and two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Although several studies examined preconception health knowledge and behaviors among some groups in Canada, such as regional childbearing-aged residents (Best Start Resource Centre, 2009b;Einarson and Koren, 2006;Tough et al, 2007), women at high risk (Huynh et al, 2012;Lipscombe et al, 2011;Murphy et al, 2010), immigrant women as a whole (Han et al, 2009), and health care providers (Best Start Resource Centre, 2009c;Ng and Newbold, 2011;Suzanne, 2004), Chinese immigrants' preconception health issues have not been well documented in the literature. Therefore, to examine the knowledge and attitudes/beliefs toward preconception health care among the Chinese immigrants in Canada, and to identify significant variables that may influence their behaviors related to preconception health and barriers that may prevent the use of preconception care, the following research questions are posed: Theoretical framework: the health belief model (HBM)…”
Section: Fertility Behavior and Health Of Chinese Immigrants In Canadamentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies examined preconception health knowledge and behaviors among some groups in Canada, such as regional childbearing-aged residents (Best Start Resource Centre, 2009b;Einarson and Koren, 2006;Tough et al, 2007), women at high risk (Huynh et al, 2012;Lipscombe et al, 2011;Murphy et al, 2010), immigrant women as a whole (Han et al, 2009), and health care providers (Best Start Resource Centre, 2009c;Ng and Newbold, 2011;Suzanne, 2004), Chinese immigrants' preconception health issues have not been well documented in the literature. Therefore, to examine the knowledge and attitudes/beliefs toward preconception health care among the Chinese immigrants in Canada, and to identify significant variables that may influence their behaviors related to preconception health and barriers that may prevent the use of preconception care, the following research questions are posed: Theoretical framework: the health belief model (HBM)…”
Section: Fertility Behavior and Health Of Chinese Immigrants In Canadamentioning
confidence: 99%
“…Guided by it, public health units implemented a series of province-wide strategies to promote preconception health across Canada, including awareness campaigns, resource releases, and education classes (Best Start Resource Centre, 2009a). Also, some research has been conducted to determine the degree to which preconception health care has been perceived by different target groups in Canada, such as regional childbearing-aged residents (Best Start Resource Centre, 2009b;Einarson and Koren, 2006;Tough et al, 2007), women at high risk (Huynh et al, 2012;Lipscombe et al, 2011;Murphy et al, 2010), and health care providers (Ng and Newbold, 2011). However, most of these studies do not pay attention to ethnic minority populations, and as such, very little is known about the viewpoints of these population groups in relation to reproductive health issues.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of information about conception planning and pregnancy for those wishing to have children (Huynh et al, 2012). Ndlovu et al (2009) found evidence of inadequate knowledge among people living with HIV (PLWHIV) about pregnancy, despite having regular access to a healthcare professional, and reported that ethnicity influenced the degree of knowledge.…”
Section: Preconception Considerationsmentioning
confidence: 99%
“…Ndlovu et al (2009) found evidence of inadequate knowledge among people living with HIV (PLWHIV) about pregnancy, despite having regular access to a healthcare professional, and reported that ethnicity influenced the degree of knowledge. PLWHIV and healthcare providers globally have indicated that access to clinical guidelines, pamphlets, workshops and peer-counselling and support are important tools to optimise the care of PLWHIV during preconception and conception (Fakoya et al, 2008; Huynh et al, 2012). Preconception and conception guidelines currently available across Europe, Canada and USA are outlined in Table 2.…”
Section: Preconception Considerationsmentioning
confidence: 99%
“…However, both guidelines acknowledge that facilities for safe reproduction for PLWHA are limited and the capacity to provide support is insufficient (Fakoya et al 2008, Loutfy et al 2012a. Several literature reviews have likewise identified a gap between the reproductive needs of PLWHA and service provision in North America, Australia and the UK (Fakoya et al 2008, Huynh et al 2012Loutfy et al 2012aLoutfy et al , 2012b Overall, within HIV programmes around the world, there is a historic lack of recognition of PLWHA's reproductive needs and the importance of reproduction to many adult gender roles. Even in the regions where this recognition is present health services are struggling to adjust and provide appropriate services.…”
Section: A Focus On Hiv and Reproductive Healthmentioning
confidence: 99%